Development of Digital Comic on Thematic Learning to Improve Literature Skills of 5th Grade Students in Elementary School - Kartika Sari, Pratiwi; Arofatinajah, Siti; Fajarianto, Otto (JTP - Jurnal Teknologi Pendidikan, 2022)
The development of information technology is very influential in the world of education, so that it can be used as a medium of learning. One way to improve the quality of education through technology is by organizing digital literacy. Digital literacy teaches a person to operate digital technology and think critically. Digital comics are one of the media that can improve students’ literacy skills. This study aims to (1) determine the development of digital comics on student literacy, (2) determine the feasibility of the digital comic product being developed, (3) determine the effectiveness of the developed digital comic product. The research method used is research and development which refers to the Richey and Klein development model using three stages, namely: planning, production, and evaluation. The research was conducted for grade V elementary school students, before being tested on students the product was evaluated first by media experts, linguists, and material experts. The results of the assessment of the media expert obtained a score of 92.85% in the very good category, the linguist got a score of 80% in the good category, the material expert got a score of 94.23% with the very good category. Based on the results of experts, digital comic media is said to be very feasible. Furthermore, the one to one test got a score of 93.06% in the very good category and the small group test got a score of 92.08% in the very good category, so the product was said to be very feasible. Meanwhile, the effectiveness test of conducting the T test with the pretest and posttest obtained a value of 0,000 < 0,05. So it is concluded that digital comic media can improve student learning outcomes and can improve student literacy skills.